Growth process control produces high-crystallinity and complete-reaction perovskite solar cells. Issue 59 (30th September 2020) - Kuan, Chun-Hsiao; Kuo, Po-Tsun; Hou, Cheng-Hung; Shyue, Jing-Jong; Lin, Ching-Fuh
Abstract : The growth process control (GPC) method, a new method which is better than thermal evaporation, for producing high-crystallinity perovskites by controlling the growth time in a low vacuum, is explored in this work. Abstract : The growth process control (GPC) method, a new method which is better than thermal evaporation, for producing high-crystallinity perovskites by controlling the growth time in a low vacuum, is explored in this work. Inspired by evaporation technology, GPC is an effective method for modifying traditional thermal evaporation and for controlling the crystal growth of perovskite CH3 NH3 I3 . Compared to fabrication with the process of co-evaporation, the MAPbI3 perovskite solar cell fabricated by GPC has high uniformity and film coverage. All of the manufacturing is carried out outside of the glove box. It provides an easy and effective way for perovskite fabrication for industrialization. Here, after using GPC to form perovskite solar cells, the residual methylammonium iodide (MAI) and PbI2 which is produced by the evaporation process can react completely, observed by time of flight secondary ion mass spectrometry (TOF-SIMS). Finally, formed by GPC, perovskite solar cells exhibit high performance and fewer crystal defects. The electron and hole recombination is greatly reduced. Through the GPC method, the J sc and the filling factor are improved with the increase of time after the fabrication. The power conversion efficiency was increased from 11.12% to 16.4%.